Therapies for Chronic Allograft Rejection - Kim, Min Young; Brennan, Daniel C. (Frontiers in Pharmacology, 2021)
Remarkable advances have been made in the pathophysiology, diagnosis, and treatment of antibody-mediated rejection (ABMR) over the past decades, leading to improved graft outcomes. However, long-term failure is still high and effective treatment for chronic ABMR, an important cause of graft failure, has not yet been identified. Chronic ABMR has a relatively different phenotype from active ABMR and is a slowly progressive disease in which graft injury is mainly caused by de novo donor specific antibodies (DSA). Since most trials of current immunosuppressive therapies for rejection have focused on active ABMR, treatment strategies based on those data might be less effective in chronic ABMR. A better understanding of chronic ABMR may serve as a bridge in establishing treatment strategies to improve graft outcomes. In this in-depth review, we focus on the pathophysiology and characteristics of chronic ABMR along with the newly revised Banff criteria in 2017. In addition, in terms of chronic ABMR, we identify the reasons for the resistance of current immunosuppressive therapies and look at ongoing research that could play a role in setting better treatment strategies in the future. Finally, we review non-invasive biomarkers as tools to monitor for rejection.